ROLE OF COMPOST AND IRRIGATION WATER QUANTITY ON SOME PHYSICAL PROPERTIES OF SOIL UNDER SURFACE, SUBSURFACE DRIP IRRIGATION - & et al., Al-Shamari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A field experiment was conducted in Ramadi district - Al-Anbar province during the autumn season of 2018. to study the role of compost (sheep residues) and irrigation levels in some physical properties of soil and water consumption a potato under surface and subsurface drip irrigation system. Randomized Complete Block Design (RCBD) in arrangement of a split- split-plot with three replication were used.The results showed that the addition of 10 Mg.h-1 resulted in a significant decrease in bulk density (BD) values of 1.12 Mg m-3, and increase in the values of (MWD) and (Ks) to reach 1.47 mm and 10.3 cm. hr -1 respectively. The addition of 50% of the NID reduced the BD to 1.24 Mg m-3, The MWD and SHC were significantly higher to reach 1.24 mm and 8.1 cm hr-1 respectively. WHC increased with increasing of amount of irrigation water as it reached the highest value of 265.66 mm season-1 when adding 100% of the NID. The BD values decreased, whereas MWD and SWC increased under subsurface irrigation (SUBDI) treatment to be 1.23 Mg m-3, 1.24 mm and 8.4 cm hr-1, respectively.